Favourable impact of statin use on diastolic blood pressure levels: analysis of a large database of 24-hour ambulatory blood pressure monitoring. Issue 10 (October 2017) - Tocci, Giuliano; Presta, Vivianne; Citoni, Barbara; Figliuzzi, Ilaria; Coluccia, Roberta; Battistoni, Allegra; Musumeci, M. Beatrice; De Biase, Luciano; Ferrucci, Andrea; Volpe, Massimo
Abstract : Introduction: Assumption of lipid-lowering drugs, mostly statins, is recommended at bed-time and evidence demonstrated a strong and independent correlation between night-time blood pressure (BP) and increased risk of cardiovascular events. Aim: To evaluate the effects of statins on night-time BP levels. Methods: We analysed data derived from a large cohort of adult individuals, who consecutively underwent home, clinic and ambulatory BP monitoring at our Unit. All BP measurements were performed and BP thresholds were set according to recommendations from European guidelines. Study population was stratified according to statin use. Results: We included an overall sample of 5634 adult individuals (women 48.9%, age 60.5 ± 11.6 years, BMI 27.0 ± 4.6 kg/m 2, clinic BP 144.3 ± 18.4/90.9 ± 12.4 mmHg, 24-h BP 130.7 ± 13.4/79.0 ± 9.7 mmHg), among whom 17.3% received and 82.7% did not received statins. Treated outpatients were older, had higher BMI and prevalence of risk factors and comorbidities than those who were untreated ( P < 0.001 for all). Patients treated with statins showed lower DBP levels at all BP measurements, including night-time (67.3 ± 9.4 vs. 70.9 ± 9.7 mmHg; P < 0.001) periods, than those observed in untreated patients. Also, statin use resulted an independent factor associated with 24-h [odds ratio (95% confidence interval): 1.513(1.295–1.767); P < 0.001] and night-time [odds ratio (95% confidence interval): 1.357(1.161–1.587); P < 0.001] BP control, even after adjusting for age, sex, BMI, diabetes, number of antihypertensive drugs (model 1) or presence/absence of antihypertensive treatment (model 2). Conclusion: Statin use was associated with significantly lower DBP levels. These effects were independently observed, even after correction for cardiovascular risk factors and comorbidities, as well as number of antihypertensive drugs. Abstract : Supplemental Digital Content is available in the text